SWOT Analysis of Cafe Di.Kayu Wangi in the Context of Tourism Village - Lukitawati, Berliana; Zainuri; Irsyadi, M.Tegar (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The culinary business is a promising one because food is a top priority in fulfilling basic human needs. However, it cannot be denied that the food business also has weaknesses and threats. This study aims to determine the marketing communication strategy of this restaurant in the context of a tourist village using a SWOT analysis. The growth of tourist villages in Indonesia shows an increasing trend, along with development based on local wisdom. This condition has encouraged the emergence of various Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector as a tourist attraction. However, this trend also presents challenges in the form of increasingly fierce competition between cafes. Café di. Kayuwangi as one of the culinary MSMEs in the ecotourism village area in Banyu Biru, Central Java, needs to have the right marketing communication strategy in order to survive and grow. The research method uses a quantitative descriptive approach, through observation, interviews, documentation, and questionnaires. The results of the study show that Café di.Kayuwangi is positioned in quadrant 1 (effective/progressive strategy), cell II in the IE Matrix, namely the Grow and Build category. Through the TOWS Matrix, four alternative marketing communication strategies were obtained: (1) an aggressive strategy with tourism and culinary integration, (2) a turn around strategy through digital branding and menu innovation, (3) a diversification strategy by strengthening local facilities and partnerships, and (4) a defensive strategy with service diversification and environmental risk management, while anticipating weaknesses and threats of competition.